A fly for the prosecution : how insect evidence helps solve crimes - Goff, M. Lee (Madison Lee) (Harvard University Press, 2000)
"Using actual cases on which he has consulted, Goff shows show knowledge of insects and their habits allows forensic entomologists to furnish investigators with crucial evidence about crimes. Even when a body has been reduced to a skeleton, insect evidence can often provide the only available estimate of the postmortem interval, or time elapsed since death as well as clues to whether the body has been moved from the original crime scene and whether drugs have contributed to the death"--Jacket.